Association Between Quantitative DOG1 and CD117 mRNA Expression and Serum Inflammatory Biochemical Markers in Gastrointestinal Stromal Tumors: DOG1/CD117 mRNA and Inflammatory Biochemistry in GIST - Yang, Jianqi; Cao, Jin; Cao, Wenmiao; Liang, Yichen (Journal of Medical Biochemistry, 2026)
Objective: To investigate the quantitative mRNA expression levels of DOG1 and CD117, two key diagnostic markers in gastrointestinal stromal tumors (GISTs), and to assess their correlations with serum inflammatory biochemical markers measured by standardized laboratory assays, so as to clarify their value in laboratory-based risk stratification of GIST and provide a quantitative basis for improving the biochemical evaluation system for this disease.Methods: A total of 110 patients with primary GIST who were scheduled to undergo radical surgery were enrolled. Tumor tissues and matched adjacent tissues obtained during surgery were analyzed by qRT-PCR to quantify DOG1 and CD117 mRNA expression. Serum levels of CRP, IL-6, TNF-α, and SAA were also measured, and the correlations between gene expression and inflammatory markers were assessed. Receiver operating characteristic (ROC) curve analysis and the Kaplan-Meier method were then used to evaluate the predictive value of gene expression for 1-year all-cause mortality.Results: Compared with matched adjacent normal tissues, GIST tissues showed significantly higher DOG1 mRNA expression (2.67±0.69 vs 1.23±0.37) and CD117 mRNA expression (2.06±0.61 vs 1.14±0.31) (P
Keywords: Gastrointestinal stromal tumor; DOG1; CD117; quantitative real-time PCR; inflammatory biomarkers; medical biochemistry